2005
DOI: 10.1016/j.schres.2005.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory deficits, cognition and negative symptoms in early onset psychosis

Abstract: SID existed across this sample of youths with psychotic disorder, and were specifically related to typical characteristics of schizophrenia, such as negative symptoms and lower intelligence, but not to features of bipolar disorder, such as grandiosity. SID is a characteristic of early onset psychosis that may be useful for prognostic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
71
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 57 publications
11
71
3
4
Order By: Relevance
“…More recently, Cowen and Green 59 have drawn attention to some parallels between schizophrenia and Kallmann's syndrome, including the fact that olfactory dysfunctions (that is, smell identification deficits) are present in a subgroup of patients with schizophrenia. 60 Versiani et al 61 also confirm the association of Kallmann's syndrome and schizophrenia, and abnormalities of cognition and behavior such as learning disabilities. However, other authors consider that this association is rare and confined to olfactory dysfunction.…”
Section: Chromosome 8p Neuropsychiatric Disorders and Cancermentioning
confidence: 91%
“…More recently, Cowen and Green 59 have drawn attention to some parallels between schizophrenia and Kallmann's syndrome, including the fact that olfactory dysfunctions (that is, smell identification deficits) are present in a subgroup of patients with schizophrenia. 60 Versiani et al 61 also confirm the association of Kallmann's syndrome and schizophrenia, and abnormalities of cognition and behavior such as learning disabilities. However, other authors consider that this association is rare and confined to olfactory dysfunction.…”
Section: Chromosome 8p Neuropsychiatric Disorders and Cancermentioning
confidence: 91%
“…Previous research has found links between olfactory identification and negative symptoms in schizophrenia (19,20,22). A recent study that examined this relationship in schizophrenia showed that the overall link between smell identification deficits and negative symptoms was driven primarily by diminished social drive, and particularly by lack of spontaneity and flow of conversation and impaired volition (46).…”
Section: Olfactory Identificationmentioning
confidence: 98%
“…Studies of olfaction in individuals with schizophrenia have demonstrated that odor identification deficits are related to negative symptoms in the disorder, such as social impairment, affective flattening, and avolition (19)(20)(21)(22). Because of the similarities between these symptoms in schizophrenia and autism (23)(24)(25), we were interested in whether olfaction was related to social impairment in autism as well.…”
mentioning
confidence: 99%
“…This reduced ability is modality-specific (Kopala et al, 1995) and seems to be most prominent in male patients (Hurwitz et al, 1988;Kopala et al, 1989Kopala et al, , 1992Coleman et al, 2002), and in patients with negative symptoms (Brewer et al, 1996;Seckinger et al, 2004;Corcoran et al, 2005). A genetic predisposition to olfactory identification deficits in psychosis has been proposed (Kopala et al, 1998(Kopala et al, , 2001, corresponding to the hypothesis that the reduced ability to identify odors might be a premorbid marker for schizophrenia (Brewer et al, 2003;Park and Schoppe, 1997).…”
Section: Introductionmentioning
confidence: 99%